Impact of Elicitation by Methyl Jasmonate and Ethephon on Cotton (Gossypium Hirsutum L.) Protection Against Fusarium Oxysporum F. Sp. Vasinfectum - Hilaire, Kouakou Tanoh; Laurent, Ncho Achi; Edwige Salomé, Yapo Sopie; Georges Elisée, Amari Ler-N’Ogn Dadé (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
The objective of the study was to evaluate the effect of methyl jasmonate and ethephon on cotton against Fusarium wilt. As well, cotton plants were treated in the field by methyl jasmonate (MeJA), ethephon (ETH) and the association of methyl jasmonate and ethephon (MeJA + ETH) and inoculated by Fusarium oxysporum f. sp. Vasinfectum (FOV). The incidence of the disease caused by FOV was evaluated every 10 days up to the 150th day after inoculation. The protection afforded to cotton following treatment by stimulators was assessed by determining the mortality rate of plants treated and inoculated FOV compared with untreated and inoculated controls. The degree of protection of cotton from Fusarium wilt was also determined through growth parameters, foliar pigment content (Chlorophylls and carotenoids) and an evaluation of the rate of lines. The results showed better protection of the cotton plants treated by the stimulators and inoculated by FOV through an increase in the number of healthy leaves, stem height, and stem diameter. This protection was also confirmed by an increase in photosynthetic activity of plants and a reinforcement of cell walls. The combination of these two molecules (MeJA + ETH) was better to induce this resistance against FOV compared to each of the two taken separately. The use of natural defence stimulators (SDN) is therefore an effective means of protecting cotton from FOV. Their application in the agricultural environment could contribute to the development of a well-reasoned, sustainable agriculture that is more respectful of the environment and human health.